Prevalence of cervical pathogens in women with and without inflammatory changes on smear testing. Issue 6886 (1st May 1993) - Parsons, W L; Godwin, M; Robbins, C; Butler, R
Abstract : OBJECTIVE--To assess correlation between nonspecific cervicitis, inflammation, or exudate on cervical smears tests and confirmed presence of known cervical pathogens. DESIGN--Investigation of women attending a family practice clinic for smear test by microbiological screening for Chlamydia trachomatis, Mycoplasma hominis, Ureaplasma urealyticum, Trichomonas vaginalis, Candida species, group B streptococcus, Gardnerella vaginalis, and Neisseria gonorrhoeae. SETTING--Family practice teaching clinic in a university hospital. PATIENTS--411 women presenting for a smear test. MAIN OUTCOME MEASURES--Prevalence of genital infections associated with presence or absence of inflammatory changes on cervical smear. RESULTS--Of the 132 women with inflammatory changes on cervical smear, 64 (48%) had positive cultures. Of the 248 without inflammatory changes, 117 (47%) had positive cultures. Subgroup analysis on individual organisms also showed no significant difference between the two groups. CONCLUSION--Reports of inflammatory changes on cervical smear testing are a poor indicator of infection.